2012
DOI: 10.1111/j.1471-4159.2012.07890.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of P‐glycoprotein and Bcrp at the rat blood–brain barrier following a subchronic morphine treatment is mediated through NMDA/COX‐2 activation

Abstract: Subchronic morphine treatment induces P‐glycoprotein (P‐gp) up‐regulation at the blood–brain barrier. This study investigates the rate and extent to which P‐gp and breast cancer‐resistance protein (Bcrp) increase at the rat blood–brain barrier following subchronic morphine treatment. Rats were given increasing doses of morphine (10–40 mg/kg) or saline i.p. twice daily for 5 days. The brain cortex large vessels and microvessels were then mechanical isolated 6, 9, 12, 24, and 36 h after the last injection. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 58 publications
(118 reference statements)
4
43
1
Order By: Relevance
“…11,23 The aim of this new work was to know whether morphine itself or its subsequent precipitated withdrawal syndrome was responsible for P-gp and Bcrp upregulation in the rat BBB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,23 The aim of this new work was to know whether morphine itself or its subsequent precipitated withdrawal syndrome was responsible for P-gp and Bcrp upregulation in the rat BBB.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerably increasing evidence that chronic exposure to morphine induces adaptive modifications including those of gene regulation and brain plasticity. [6][7][8] Interestingly, twice daily subchronic morphine exposure has been shown to increase P-gp content in rat, [9][10][11] and mouse whole brain. 5 Actually, we previously showed that P-gp expression in rat brain microvessels was only upregulated several hours after, and not immediately after, treatment suspension, following a twice daily subchronic morphine administration, which timely coincided with the beginning of a spontaneous morphine withdrawal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous in vitro and in vivo studies have shown that drugs can either modulate their own transport by P-gp (Zastre et al, 2009;Yousif et al, 2012) or the transport of other P-gp substrates (Bauer et al, 2004(Bauer et al, , 2006Wang et al, 2010;Chan et al, 2011). This consideration is critical in pharmacotherapy of pain where ancillary medications such as APAP are often combined with opioids as part of a therapeutic regimen.…”
Section: Discussionmentioning
confidence: 99%